Metode Pelaksanaan Pekerjaan Struktur Tribun dan Perhitungan Menggunakan Sap2000 Pada Proyek Pembangunan Gelanggang Generasi Muda (GGM) Majalengka - Adlan Rosyadi, Mohamad; Arief Rijaluddin (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
The tribune is a part of a sports building or stadium intended for spectators to watch matches or sporting events. The tribune usually consists of rows of chairs or benches arranged in tiers or terraces, providing a good view of the field or arena where sports activities take place. Research on the tribune structure work methods and calculations using Sap2000 was carried out on the Majalengka Young Generation Center (GGM) construction project. . The method used in this tribune structure work is cast in situ/conventional with ready mix concrete and FC quality 30 MPa. The results of the research on the method of carrying out work on the grandstand structure showed that work was done on beams & plates, then work on steps/traps. Implementation of work on beams & plates includes preparatory work which includes measurements and shop drawings, installation of scaffolding, installation of formwork, installation of reinforcement, casting assisted by buckets and tower cranes, maintenance. Then, the implementation of the steps/trap work includes measuring and marking, installing optrade, installing antrade formwork, installing reinforcement, casting antrade, finishing, installing precast traps, installing chairs. The calculations carried out are useful for knowing the forces acting on the structure of the spectator stands and to determine the safety of the structure of the stands. The author conducted research in terms of seating comfort for the audience and resulted in a lack of distance between chairs so that the legs did not only have little space or could be said to be narrow and less comfortable.